Difference in the Inhibitory Effect of Temozolomide on TJ905 Glioma Cells and Stem Cells - Jin, Feng; Han, Guang-Kui; Zhang, Hao; Zhang, Ran; Li, Gen-Hua; Feng, Song; Qin, Xian-Yun; Kong, Ling-Sheng; Nie, Quan-Min; Li, Hua-Rong; Zhao, Lei (Frontiers in Neurology, 2017)
This study aims to determine the difference in the inhibitory effect of Temozolomide on TJ905 glioma cells and stem cells. TJ905 cancer stem cells were isolated. The TJ905 cells and cancer stem cells were transfected with a Livin-shRNA and negative-shRNA, respectively, and then treated with Temozolomide. At 48 h post-transfection, a CCK-8 assay, flow cytometry and real time qPCR were performed to detect cell proliferation, the cell cycle and the expression of the Caspase 3, 7 and 9 mRNAs, respectively. As a result, the suppressive effect of Temozolomide on TJ905 cells was more significant than its effect on TJ905 cancer stem cells. Temozolomide exerted an inhibitory effect on growth of TJ905 glioma cells by arresting them at G0/G1 phase and arresting cancer stem cells at S phase in dose-dependent manner. Temozolomide inhibited Livin mRNA expression and increased the expression of the Caspase 3, 7 and 9 mRNAs. Low Livin mRNA expression obviously induced high levels of Caspase 3, 7 and 9 expression, thus promoting the apoptosis of both TJ905 cells and cancer stem cells in response to Temozolomide treatment. The TJ905 cells transfected with the Livin-shRNA were more sensitive to Temozolomide, whereas the TJ905 glioma stem cells transfected with the Livin-shRNA showed no obvious changes in their sensitivity to Temozolomide. In conclusion, the Livin gene may play an important role in the resistance mechanisms of TJ905 glioma cells and cancer stem cells. However, Livin had a more distinct role in Temozolomide resistance, cell proliferation and the cell cycle in TJ905 glioma cells than in cancer stem cells.